2001
DOI: 10.1248/cpb.49.511
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Asymmetric Catalysis.

Abstract: Two types of general and practical enantioselective catalysts, namely, bimetallic complexes and Lewis acid-Lewis base bifunctional catalysts were developed based on the concept of multifunctional catalysis. In the first part of this review, the first example of a catalytic enatioselective nitro-Mannich reaction as well as a direct catalytic enantioselective aldol reaction of 2-hydroxyacetophenone using bimetallic complexes is discussed. The new complex, composed of ytterbium, potassium, and BINOL in a ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Transfer hydrogenation using stable organic hydrogen donors such as 2-propanol or formic acid is an attractive solution to the above demand. Some recent examples include tetrahydroisoquinolines (13) [47,48] and indole alkaloids (14)(15)(16) [49]. The methodology has been applied to a numerous synthesis of optically active amines.…”
Section: Transfer Hydrogenationmentioning
confidence: 99%
“…Transfer hydrogenation using stable organic hydrogen donors such as 2-propanol or formic acid is an attractive solution to the above demand. Some recent examples include tetrahydroisoquinolines (13) [47,48] and indole alkaloids (14)(15)(16) [49]. The methodology has been applied to a numerous synthesis of optically active amines.…”
Section: Transfer Hydrogenationmentioning
confidence: 99%
“…[46][47][48]. For example, Hoveyda and coworkers reported asymmetric addition of TMSCN (trimethylsilyl cyanide) to aromatic and aliphatic ketones catalyzed by bifunctional aluminum-complex 1 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation into the mechanism of carboxypeptidase A and aldolase has revealed that a Lewis acid acting in concert with a Brønsted base will effect the intramolecular enolization of ketones as shown in 1 . An exciting area of research is the design of bifunctional ligands , with noncoordinating basic groups. When these ligands are bound to a metal, the complexes behave like enzymes, combining molecular recognition with catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…While enolization of acetone was accomplished under mild, neutral conditions to generate the carbon-bound Rh enolate, the presumed lack of reactivity of the Rh enolate has prevented the development of a general catalytic system with this complex. Shibasaki and co-workers have recently described heterobimetallic lithium−lanthanum BINOL complexes which catalyze the direct aldol, nitro-aldol, and Michael reactions with good yields and enantioselectivities …”
Section: Introductionmentioning
confidence: 99%